Efforts Towards Bifunctional PZM21 Analogues as Potential Novel Analgesics - Mandato, Julia (Université d'Ottawa / University of Ottawa, 2023)
Complex pharmacological problems such as chronic pain require creative drug design that goes beyond single point binding and polypharmacology approaches. Current MOR agonists used for pain relief, notably opioid drugs, have negative side effects from activation of the β-arrestin recruitment pathway limiting their use. Pain relief through Nav channel blockers is not successful due to dangerous side effects attributed to nonselective binding. Literature evidence suggests that combined therapy of MOR biased agonists and selective Nav1.7 VSD4 blockers, either independently or as a bifunctional drug, can result in potent analgesia with limited side effects due to selective activation of secondary pathways and highly specific binding. Synergy of the two pharmacophores can additionally lead to higher potency and lower doses of less addictive pain relief drugs. This work presents efforts toward bifunctional compounds to target these two components in the pain network with one molecule. Compounds containing pharmacophores inspired by the MOR biased agonist PZM21 and aryl sulfonamide Nav1.7 VSD4 selective blockers were designed, synthesized, and tested for analgesic activity. Through three generations of SAR, 21 compounds were tested for agonist activity at MOR and 12 compounds were tested for VSD4 blocking at Nav1.7. Two compounds, 7a and 7b showed activity similar to know VSD4 blockers and two compounds 23a and 24a showed MOR agonist activity with selectivity and activation similar to PZM21. Major insight has been gained regarding the requirements of binding at each receptor including pharmacophore functionalities, flexibility, and overall orientation of the compound driven by a required conformation to bind at each receptor. The results reported in this thesis provided essential information for current work toward a bifunctional compound.
Keywords: Pain Relief; Biased MOR agonist; Nav1.7 Blocker; Bifunctional Analgesic; PZM21; Drug Design